Review of State-of-the-Art Tools for Network Analysis with NetworkX - Edyta FRĄSZCZAK (Communications of International Proceedings, 2024)
This article offers a comprehensive review of the latest tools for network analysis, focusing on methods and applications that utilize the NetworkX package. It examines recent advancements in community detection, network propagation, source identification within social networks, and strategies for identifying critical nodes. Special emphasis is placed on advanced algorithms that enhance NetworkX's functionality in dynamic environments. This review serves as a valuable resource for researchers and practitioners looking for practical and effective tools for modern network analysis. The paper provides sample usages of the described libraries, encouraging readers to utilize them effectively.
Keywords: Networks; network analysis; network data exploration; network analysis software.